Function-oriented design of robust metal cocatalyst for photocatalytic hydrogen evolution on metal/titania composites - Dong Wang (Nature Portfolio, 2021)
Photocatalytic performances require both active catalytic surfaces and efficient electron transfer steps. Here the authors introduce a function-oriented catalyst design strategy optimizing both aspects and generalize an effective electron transfer descriptor on metal/oxide catalysts.